STEM-Project Based Learning with Learning Guides on Electrolyte and Non Electrolyte Solutions to Improve Higher Order Thinking Skills of High School Students - Kartikasari, Santi; Abudarin, Abudarin (Jurnal Pendidikan MIPA, 2022)
The purpose of this study was to examine the effect of STEM-Project Based Learning with learning guides on the Concept of Electrolyte and Non-Electrolyte Solutions on the ability to think of high order students of class X SMA Negeri 3 Palangka Raya. The study used a quasi experimental method with a nonequivalent control group design. The research sample was 35 students of Class X MIPA 1 as a control class and 36 students of Class X MIPA 5 as an experimental class. STEM-Project Based Learning with learning guides is done using the help of study guides. Data collection of higher order thinking skills is carried out using tests (pretest and posttest) specifically designed to measure higher order thinking skills. The data obtained were statistically analyzed using the t test to compare the increased thinking ability of the kontrol class and the experimental class. The statistical test results obtained that tcount is greater than ttable, that is tcount = 21.74 greater than ttable = 2.032, which shows that the average increase in high order thinking skills of experimental class students is better than the average increase in the ability of thinking of control class students. Thus, it can be concluded that STEM-Project Based Learning with learning guides on the Concept of Electrolyte and Non-Electrolyte Solutions can improve higher order thinking skills. Keywords: electrolyte and non-electrolyte solutions, STEM-Project Based Learning, high order thinking. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1214-1223